Impact of Social Norms on Tax Morale in Malaysia: Empirical Evidence Through Structural Equation Modelling - Teh Suhaila Tajuddin; Izlawanie Muhammad; Mohd Adha Ibrahim (Universal Publishers - Boca Raton, Florida, USA, 2024)
Indexed by ERA